Copper-catalyzed tandem A3-coupling–isomerization–hydrolysis reactions of aldehydes and terminal alkynes leading to chalcones. Issue 3 (8th January 2016) - Zhao, Yingwei; Song, Qiuling
Abstract : A 3 coupling is not the end: catalyzed by a simple copper salt, the reaction of aldehyde, alkyne, and amine can afford chalcone. Abstract : Catalyzed by a simple copper salt, the reaction of an aryl aldehyde and a terminal alkyne in the presence of piperidine delivers the valuable chalcone products, which were rarely found in previous A 3 coupling reactions. This reaction can be applied to a wide range of substrates. Mechanistic studies indicate that this reaction experiences a tandem process containing A 3 coupling, copper assisted isomerization of propadienamine to allenylamine and subsequent hydrolysis.